Membangun Pendidikan Karakter melalui Pengimplementasikan Ecobrick pada Siswa di SMP Negeri 51 Pondok Bambu, Duren Sawit Jakarta Timur - Myta Widyastuti; Ida Rosida (Jurnal Syntax Admiration, 2024)
The increase in the number of people who are increasingly increasing and with a consumptive lifestyle causes several problems, one of which is the emergence of a lot of waste. Facing the problem of waste, recycling plastic waste is the best solution in overcoming it. Waste management is known as the "3R Principle, namely Reduce, Reuse, and Recycle. If the community is not able to manage waste. can be done by recycling plastic bottles through Ecobricks. Therefore, see how effective the understanding of environmental cleanliness is so that later it will also grow other positive sides in children. So the researcher felt interested in conducting research with the theme: Building Character Education Through the Implementation of Ecobricks in Students at SMP Negeri 51 Jakarta.